Synthesis and characterization of poly(L-lactic acid-co-ethylene oxide-co-aspartic acid) and its interaction with cells - KAYAMAN APOHAN, NİLHAN (SPRINGER, 2006)
Multiblock terpolymer of poly(L-lactic acid)/ poly(ethylene oxide)/poly(L-aspartic acid), (PLLA/PEO/ PAsp) was synthesized by ring opening polymerization of beta-benzyl L-aspartate N-carboxyanhydride, Asp(OBzl)-NCA with alpha-omega-hydroxy terminated triblock PLLA/PEO/PLLA copolymer. The resulting multiblock terpolymer was characterized by several techniques including Fourier transform infrared spectroscopy and differential scanning calorimetry. H-1 nuclear magnetic resonance spectra indicated the molar ratio of PLLA/PEO/PAsp (OBzl) to be 86/10/4. Thermal gravimetric analysis and environmental scanning electron microscopy data showed that PLLA/PEO/PAsp had crystalline and brittle structure. In order to improve its mechanical and physical properties, the terpolymer was blended with high molecular weight poly(L-lactic-co-glycolic acid) copolymer, PLGA(85/15) (M-w: 95000 gmol(-1)) in 25/75 and 50/50 mole ratios. The hydrolytical degradation properties of these polymers were studied. Degradation experiments were performed during a 48-day period in pH:7.4 phosphate-buffered saline (PBS) at 37 degrees C. The observed molecular weight losses were 91% and 67% for the 25/75 and 50/50 mixtures, respectively. In vitro attachment and growth of L929 mouse fibroblasts on these biopolymers were also investigated. Cell growth experiments indicated that the copolymer blend allowed the attachment and growth of cells.
Keywords: GRAFT-COPOLYMERS; IN-VITRO; DEGRADATION; FABRICATION; POLYMERS; ALPHA